Food applications of nanotechnology - Gustavo, Molina; Inamuddin, 1980-; Pelissari, Franciele Maria; Asiri, Abdullah M. (Boca Raton, Florida : CRC Press, 2019)
Nanotechnology has developed remarkably in recent years and, applied in the food industry, has allowed new industrial advances, the improvement of conventional technologies, and the commercialization of products with new features and functionalities. This progress offers the potential to increase productivity for producers, food security for consumers and economic growth for industries. Food Applications of Nanotechnology presents the main advances of nanotechnology for food industry development. The fundamental concepts of the technique are presented, followed by examples of application in several sectors, such as the enhancement of flavor, color and sensory characteristics; the description of the general concepts of nano-supplements, antimicrobial nanoparticles and other active compounds into food; and developments in the field of packaging, among others. In addition, this work updates readers on the industrial development and the main regulatory aspects for the safety and commercialization of nanofoods. Features: Provides a general overview of nanotechnology in the food industry Discusses the current status of the production and use of nanomaterials as food additives Covers the technological developments in the areas of flavor, color and sensory characteristics of food and food additives Reviews nanosupplements and how they provide improvements in nutritional functionality Explains the antibacterial properties of nanoparticles for food applications This book will serve food scientists and technologists, food engineers, chemists and innovators working in food or ingredient research and new product development. Gustavo Molina is associate professor at the UFVJM (Diamantina--Brazil) in Food Engineering and head of the Laboratory of Food Biotechnology and conducts scientific and technical research. His research interests are focused on industrial biotechnology. Dr. Inamuddin is currently working as assistant professor in the chemistry department of Faculty of Science, King Abdulaziz University, Jeddah, Saudi Arabia. He is also a permanent faculty member (assistant professor) at the Department of Applied Chemistry, Aligarh Muslim University, Aligarh, India. He has extensive research experience in multidisciplinary fields of analytical chemistry, materials chemistry, and electrochemistry and, more specifically, renewable energy and environment. Prof. Abdullah M. Asiri is professor of organic photochemistry and has been the head of the chemistry department at King Abdulaziz University since October 2009, as well as the director of the Center of Excellence for Advanced Materials Research (CEAMR) since 2010. His research interest covers color chemistry, synthesis of novel photochromic and thermochromic systems, synthesis of novel coloring matters and dyeing of textiles, materials chemistry, nanochemistry and nanotechnology, polymers, and plastics. Franciele Maria Pelissari graduated in Food Engineering; earned her master's degree (2009) at the University of Londrina (UEL), Londrina, Brazil; and her PhD (2013) at the University of Campinas (Unicamp), Campinas, Brazil. Since 2013, she has been associate professor at the Institute of Science and Technology program at the Federal University of Jequitinhonha and Mucuri (UFVJM), Diamantina, Brazil, in Food Engineering, and also full professor in the graduate program in Food Science and Technology.
General overview and future trends of nanotechnology in the food industry -- Agri-food sector, biological systems and nanomaterials -- Industrial developments and main companies in the food and beverage sector: from research to industry -- Engineered nanostructures for enrichment and fortification of foods -- Nanosupplements: improvements in nutritional functionality of food products -- Production and application of antibacterial nanoparticles in the food industry -- Nanoencapsulation and nanoemulsions: preparation and applications in the food industry -- Application of nanomaterials in the meat and seafood processing industry -- Nanotechnology applied to cereal grains and cereal-based products and its food safety -- Application and potential of nanotechnology in milk and derivatives processing industry -- Application of nanotechnology in alcoholic and nonalcoholic beverages -- Application of nanotechnology to food distribution and storage -- Green polymers nanocomposites applied in food packaging -- Application of nanotechnology in antimicrobial active food packaging -- Cereal bioactive components and nano encapsulation methods for enhanced bioavailability -- Nanoencapsulation of plant-based oils and its applications in food and food packaging -- Nanobiotechnology ingredients applied to the food industry -- Nanomaterials based electrochemical biosensors for aflatoxin-b1 detection: application in food safety -- Nanomaterial bound enzymes and their applications in food industry -- Enhanced microbial control of germinated seeds for the food industry using nanotechnology -- Potential application of nanopesticides towards the pest control in food and agriculture sector -- Utilization and valorization of food waste using nanotechnology approach -- Regulation and food safety of nanotechnology in the food industry.
OCLC-licensed vendor bibliographic record.
Keywords: Food -- Biotechnology; Food industry and trade -- Technological innovations; Nanotechnology; COOKING / General; TECHNOLOGY / Food Science